Quality of life after necrotizing enterocolitis: an integrative review - Breno Oliveira Marques; Ana Beatriz Ferreira Gusmão; Luana Leal Gonzaga; Gabriela Garcia de Carvalho Laguna; Níkolas Brayan da Silva Bragas; Camila da Palma Maltez Monção; Natália Oliveira e Silva (Sociedade de Pediatria de São Paulo, 2024)
ABSTRACT Objective: To describe the long-term health outcomes of neonates affected by necrotizing enterocolitis (NEC) and its implications for quality of life. Data source: This is an integrative review, conducted by searching the literature in the following databases: Virtual Health Library (BVS), Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE), and PubMed, using Health Sciences Descriptors (DeCS): "necrotizing enterocolitis," "quality of life," and "prognosis" combined with the Boolean operators AND and OR: "quality of life" OR "prognosis." Inclusion criteria were: publication period between 2012 and 2022. Data synthesis: A total of 1,010 studies were located, of which ten were selected to comprise the bibliographic sample of this review. Children with NEC are prone to exhibit cognitive neurological impairment, especially those who undergo surgical procedures due to more severe conditions. Motor development was considered below average when compared to healthy children, with more noticeable delays in fine and gross motor function development. The search for the relationship between NEC and quality of life revealed that this condition has a negative impact on the well-being of affected individuals. Conclusions: NEC has proven to be a serious condition contributing to high rates of morbidity and mortality in newborns, potentially leading to a reduction in the quality of life of affected patients.